1986
DOI: 10.1099/00222615-22-4-351
|View full text |Cite
|
Sign up to set email alerts
|

Mutagenic activation of biliary metabolites of benzo(a)pyrene by  -glucuronidase-positive bacteria in human faeces

Abstract: Summary. Human faeces hydrolysed synthetic P-D-glucuronides of both p-nitrophenol and phenolphthalein. The origin of this activity in faeces was localised in the bacterial pellet fraction after centrifugation. Ninety-seven bacterial strains with P-glucuronidase activity isolated from fresh human faeces were identified as species of Bacteroides, Peptostreptococcus, Fusobacterium, Propionibacterium, Clostridium, Eubacteriurn and Bijidobacterium. They were classified into two groups according to their activity ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

1990
1990
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…For instance, when potentially carcinogenic compounds are detoxified by UDPGT (Dutton, 1980) . /I-Glucuronidase activity has been implicated in the activation of benzo(a)pyrene and 1,2-dimethylhydrazine conjugates in the colon (Nanno et al 1986;Mallett & Rowland, 1990). It has been demonstrated that the yield of colorectal tumours is lower in germ free rats exposed to 1 ,Zdimethylhydrazine than in similarly treated conventional rats (Reddy et al 1974) and that a /I-glucuronidase inhibitor can protect rats with a conventional flora from the induction of tumours by azoxymethane, a metabolite of 1 ,Zdimethylhydrazine (Takada et al 1982).…”
Section: U N J U B a I L U N B Y Y H A S C 11 E N L Y M Cmentioning
confidence: 99%
“…For instance, when potentially carcinogenic compounds are detoxified by UDPGT (Dutton, 1980) . /I-Glucuronidase activity has been implicated in the activation of benzo(a)pyrene and 1,2-dimethylhydrazine conjugates in the colon (Nanno et al 1986;Mallett & Rowland, 1990). It has been demonstrated that the yield of colorectal tumours is lower in germ free rats exposed to 1 ,Zdimethylhydrazine than in similarly treated conventional rats (Reddy et al 1974) and that a /I-glucuronidase inhibitor can protect rats with a conventional flora from the induction of tumours by azoxymethane, a metabolite of 1 ,Zdimethylhydrazine (Takada et al 1982).…”
Section: U N J U B a I L U N B Y Y H A S C 11 E N L Y M Cmentioning
confidence: 99%
“…In the group of PAHs, B(a)P has the highest potential to cause cancer [2,4,8,9]. Furthermore, B(a)P has also mutagenic and teratogenic effects [2,6,[10][11][12]. It transforms into (+)-BP-7-8-oxide by the monooxigenase enzyme, into (-)-trans-BP-7,8-dihydrodiol by the epoxide hydrolase enzyme and into (+)-anti-BP-7,8-diol-9,10-epoxide by the monooxigenase enzyme [1,5].…”
Section: Introductionmentioning
confidence: 99%
“…Po lar conjugates, including the glucuronide, are excreted into bile after the administration of BaP to rodents [15] and hydrolyzed to BaP diols and BaP by intestinal microorganisms. These products are directly mutagenic in bacterial test systems [16] and bind to DNA in vitro [17], whereas hepatic conjugates of BaP show no genotoxic activity when P-gluc uronidase activity is absent [18]. These ob servations suggest that bacterial products formed from BaP in the large intestine are potential candidates as initiators of the car cinogenic transformation of mucosal cells.…”
Section: Hydrolysis Of Glucuronide Conjugatesmentioning
confidence: 91%